Assessment of petroleum biodegradation using stable hydrogen isotopes of individual saturated hydrocarbon and polycyclic aromatic hydrocarbon distributions in oils from the Upper Indus Basin, Pakistan - Asif, Muhammad; Grice, Kliti; Fazeelat, T. (Elsevier Science, 2009)
The stable hydrogen isotopic compositions (dD) of selected aliphatic hydrocarbons (n-alkanes and isoprenoids) in eight crude oils of similar source and thermal maturity from the Upper Indus Basin (Pakistan) were measured. The oils are derived from a source rock deposited in a shallow marine environment. The low level of biodegradation under natural reservoir conditions was established on the basis of biomarker and aromatic hydrocarbon distributions. A plot of pristane/n-C17 alkane (Pr/n-C17) and/or phytane/n-C18 alkane (Ph/n-C18) ratios against American Petroleum Institute (API) gravity shows an inverse correlation. High Pr/n-C17 and Ph/n-C18 values and low API gravity values in some of the oils are consistent with relatively low levels of biodegradation. For the same oils, dD values for the n-alkanes relative to the isoprenoids are enriched in deuterium (D). The data are consistent with the removal of D-depleted low molecular weight (LMW) n-alkanes (C14-C22) from the oils. The dD values of isoprenoids do not change with progressive biodegradation and are similar for all the samples. The average D enrichment for nalkanes with respect to the isoprenoids is found to be as much as 35% for the most biodegraded sample. The relative susceptibility of alkyl naphthalenes at low levels of iodegradation is discussed. The alkyl naphthalene biodegradation ratios were determined to assess the effect of biodegradation. The dimethyl, trimethyl and tetramethyl naphthalene biodegradation ratios show significant differences with increasing extent of biodegradation.